Boron in geothermal energy: Sources, environmental impacts, and management in geothermal fluid. (October 2022) - Mott, A.; Baba, A.; Hadi Mosleh, M.; Ökten, H.E.; Babaei, M.; Gören, A.Y.; Feng, C.; Recepoğlu, Y.K.; Uzelli, T.; Uytun, H.; Morata, D.; Yüksel, A.; et al.
Abstract: The problem of hazardous chemicals in geothermal fluid is a critical environmental concern in geothermal energy developments. Boron is among the hazardous contaminants reported to be present at high concentrations in geothermal fluids in various countries. Poor management and inadequate treatment of geothermal fluids can release excessive boron to the environment that has toxic effects on plants, humans, and animals. Despite the importance of boron management in geothermal fluid, limited and fragmented resources exist that provide a comprehensive understanding of its sources, transport and fate, and the treatment strategies in geothermal energy context. This paper presents the first critical review from a systematic and comprehensive review on different aspects of boron in geothermal fluid including its generation, sources, toxicity, ranges and the management approaches and treatment technologies. Our research highlights the origin of boron in geothermal water to be mainly from historical water-rock interactions and magmatic intrusion. Excessive concentrations of boron in geothermal fluids have been reported (over 500 mg/L in some case studies). Our review indicated that possible boron contamination in geothermal sites are mostly due to flawed construction of production/re-injection wells and uncontrolled discharge of geothermal water to surface water. The dominancy of non-ionic H3 BO3 species makes the selection of the suitable treatment method for geothermal waters limited. Combining boron selective resins and membrane technologies, hybrid systems have provided effluents suitable for irrigation. However, their high energy consumption and course structure of boron selective resins encourage further research to develop cost-effective and environmentally friendly alternatives. Graphical abstract: Image 1 Highlights: Boron in geothermal originates from water-rock interactions and magmatic intrusion. Non-ionic H3 BO3 in geothermal water limits the water treatment methods. Flawed wells and uncontrolled discharge of water is common source of contamination. Cost-effective treatments are limited for boron removal in geothermal waters.